Tratamento de lixiviado de aterro sanitário por processo fenton: Identificação dos compostos orgânicos, caracterização do lodo e ensaios ecotoxicológicos - Dantas, Edilma Rodrigues Bento (2018)
The leachates are characterized by a high organic load, inorganic macro pollutants, heavy metals and xenobiotic organic compounds that, even when present in low concentrations, give the significant leachate a high polluting power. One of the current challenges, from an environmental point of view, is to treat leachate from landfills efficiently, mainly due to the heterogeneity of its composition, which can vary from landfill to landfill, depending on the age of the landfill. Due to this large variation in composition, conventional treatments using biological processes are not sufficient to meet the current release standards, especially when the leachate is old. An alternative to the treatment of landfill leachate is the use of Advanced Oxidative Processes (POAs) which are characterized by the production of powerful oxidizing agents, such as hydroxyl radicals (OH •). There are several types of POA, but one that stands out is the Fenton process, since its viability for the treatment of leachates is due to the simplicity of its application, because the reactions occur at the temperature and pressure environments, they need reagents and equipment simple and act in a non-selective manner causing the mineralization of several compounds. The present study aimed to use the Fenton process in the treatment of landfill leachate in the municipality of Puxinanã in the state of Paraíba. The study comprised the characterization of the crude and treated leachate and the sludge formed and the ecotoxicity tests of the supernatant. In the first step of the conventional characterization, it was observed that the Fenton process was efficient in removing 87% of the COD, 98% of the actual color, 74% of COD and removal of more than 70% of BOD. The BOD/COD ratio of the treated leachate doubled. The sludge production rate was approximately 98 kg / m 3, 89% moisture and moderate specific resistance to filtration (12x10^9cm/g). 152 organic compounds were identified in the crude leachate. Of these, 80% were removed by the Fenton process, which resulted in a leachate treated with 83 organic compounds of which 30 compounds were not removed and 53 new compounds were generated. Toxicological tests demonstrated that although Fenton treatment achieved good efficiency in removal of various physico-chemical parameters and increased the BOD/COD ratio to 0.7, the treated leachate still remained toxic. The treated leachate is three times more toxic to the Daphnia magna bioindicator than the crude leachate. The BMP test showed that the biogas production in the treated leachate is 19 L/gDQO and in the crude leachate is 3 L/gDQO under the same conditions. The respirometry test showed that in the treated leachate the COD is slowly biodegradable is higher than 90%, which resulted in a 20% decrease in TCO by the microorganisms.